A multicentre Canadian survey of caregiver perspectives on COVID vaccine-related pain and stress for their family. Issue 5 (October 2022) - Ali, Samina; Kammerer, Elise; Thompson, Graham; Mater, Ahmed; Rajagopal, Manasi; Bone, Jeffrey N; Birnie, Kathryn A; Oberlander, Tim; Chambers, Christine T; Goldman, Ran D; ,
Background: Caregiver hesitancy for their children to receive the COVID-19 vaccine remains due to concerns regarding safety and efficacy, but also due to fear of vaccine administration-related pain and distress. Study objectives were to determine caregivers' perceptions regarding both their personal and child's COVID-19 vaccine administration-related stress and fear and relate this to their likelihood to allow their child to receive COVID-19 vaccinations. Methods: This study was a secondary data analysis of a multicentre, cross-sectional survey of caregivers presenting to four Canadian pediatric emergency departments. Caregivers were surveyed between December 2020 and March 2021 and completed a digital survey on their own smartphones. Results: 331 caregivers responded to the survey (mean age 39.9 years [SD 7.71]); 74.2% (245/331) were mothers. Children's mean age was 8.8 years [SD 5.4]; 49.8% (165/331) were female. 64.1% (209/326) of caregivers were willing to vaccinate their child against COVID-19, while 35.9% (117/326) were not. Greater perceived COVID-19 vaccine administration-related pain (0.88 [0.80; 0.95], p = .003) and stress (0.82 [0.76; 0.89], p = <.001) for their child as well as greater perceived personal stress with their own COVID-19 vaccine administration (0.81 [0.75; 0.88], p = <.001) were associated with caregivers being less likely to vaccinate their child. Conclusions: During the time period between COVID-19 pandemic waves 2 and 3, and after the vaccine had been federally approved for adults, one-third of Canadian caregivers surveyed reported being unwilling to vaccinate their child against COVID-19 in the future. Managing children's and caregivers' vaccine administration-related fear and stress may improve vaccine uptake for children.